War fund dinner - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows several men seated at round tables. Six women sit at a long table in the front of the room, and six men stand behind them. On the wall behind the long table is a sign with a red cross which reads: "War fund." On either side of the long table are two displays of cans. The labels on the cans read: "Red Line lubricating grease. Union Oil Company." On the left side of the photograph the sign reads: "Weak batteries waste gas! Let us check yours." On the right side of the photograph the sign reads: "Dirty plugs waste gas! We clean [&] adjust, 5 cents ea."